2017
DOI: 10.1179/1743294415y.0000000090
|View full text |Cite
|
Sign up to set email alerts
|

Sliding wear behaviour and its mechanisms of carbonitrided AISI 8620 steel at 100°C under unlubricated conditions

Abstract: This paper deals with high temperature dry sliding wear behaviour and its mechanism of carbonitrided AISI 8620 steel. The sliding wear behaviour of the carbonitrided AISI 8620 steel was investigated using a pin on disc equipment at 1008C with varying parameters like normal load and sliding velocity. The scanning electron microscopy features of the worn samples reveal that abrasion with shallow and narrower wear track is the dominant wear mechanism of carbonitrided AISI 8620 at 50 N, while at 150 N, plastic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…SEM surveys of wear tracks formed at high testing load of 4 N, revealed that the unalloyed PTA specimen has undergone severe damage wherein carbides are not only cracked but also removed during the progress of wear. Besides there is evidence for severe ploughing and stair casing (as a result of fatigue wear) as observed in earlier studies [36][37][38][39]. This should be noted that at higher testing load of 4 N, the As PTA Stellite 12 specimen is unable to resist carbide cracking and removal due to nature of coarse Cr-rich carbides [26].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…SEM surveys of wear tracks formed at high testing load of 4 N, revealed that the unalloyed PTA specimen has undergone severe damage wherein carbides are not only cracked but also removed during the progress of wear. Besides there is evidence for severe ploughing and stair casing (as a result of fatigue wear) as observed in earlier studies [36][37][38][39]. This should be noted that at higher testing load of 4 N, the As PTA Stellite 12 specimen is unable to resist carbide cracking and removal due to nature of coarse Cr-rich carbides [26].…”
Section: Discussionsupporting
confidence: 65%
“…For the Mo-added ‘As PTA’ specimen there has been clear evidence of plastic damage resulting in ploughing and stair casing [36-39]. However, the carbide cracking and removal is still absent in this specimen due to larger volume fractions of crack-resistant complex carbides.…”
Section: Discussionmentioning
confidence: 99%
“…The lubricating effect of the oxide film was beneficial to reducing the wear rate, which also resulted to a lower friction coefficient and a smaller material loss. In the final stage, the principal mechanism of friction was the delamination wear [29]. In this stage, continuous cutting induced oxide film spalling from the surface of Zr-Y alloyed layer and then a new bare surface oxidised again, entering to a new circle.…”
Section: Wear Propertiesmentioning
confidence: 99%
“…The effects of ammonia flow rate on the microstructure, distortion, hardness and strength have been investigated, but still focused on the low carbon steel [16] . Abrasion with shallow and narrower wear track was the predominant wear mechanism of carbonitrided AISI 8620 at 50 N; whereas, high friction sliding mechanism at 150 N was controlled by plastic deformation [17] . However, the microstructure evolution on high carbon chromium bearing steel during carbonitriding and the friction behavior of carbonitrided specimens are extremely meager and uncomprehensive.…”
Section: Introductionmentioning
confidence: 96%